The Intellectual Landscape of Teacher Burnout Research: Evidence from Scopus Publications - Moh. Badrut Tamam; Andi Nuzul Akbar; Asmansyah (Suria Academic Press, 2026)
This study maps the intellectual landscape of burnout research indexed in Scopus, highlighting how the field has evolved, where it is published, what themes dominate, and which methodological and geographic patterns shape the literature. A bibliometric study was conducted using Scopus metadata covering 1,421 English journal articles from 2020–2025. The analysis integrates performance analysis, annual publication trends, source productivity, and local source impact using the H-index within the corpus, science mapping three-field plot and word-frequency mapping or word cloud, complemented by corresponding-author country distribution to describe geographic contribution and collaboration patterns. The literature shows steady growth with a marked acceleration after 2022, rising from 167 publications in 2020 to 340 in 2025. Output is distributed across multiple key outlets, with strong visibility in education, behavioral science, and health-related journals. Local source impact indicates a small set of journals function as central knowledge anchors in the corpus. Thematic mapping confirms burnout as the core topic, strongly connected to psychology, mental health, job satisfaction, and related occupational outcomes. Methodologically, the field is dominated by cross-sectional survey designs, while mediator or moderator testing is a growing analytical trend. The study provides a consolidated evidence map to clarify research directions, dominant themes, and underexplored opportunities for future studies and collaborations.